The I LAURANG THE SHRIMP MAN'S INSPIRATION IN GALA PARTY ATTIRE - Sugiyem - Sugiyem (Jurnal Da Moda, 2023)
Fashion is one of the human needs that never runs out to be explored. Exploration of party fashion with the source of cultural ideas can result in unique, creative, and meaningful fashion designs. Developing party fashion with the source of Indonesian cultural ideas is very important because it can enrich party fashion designs and provide more value to fashion. Gala party clothing with the source of the idea I Laurang Sang Manusia Udang indirectly introduces Sulawesi folklore in which there is a moral story about sincerity, patience, never giving up, and confidence which ultimately results in victory and happiness. Creating culturally inspired clothing and exploring culture as a source of fashion creation ideas is important because it can help maintain cultural heritage, create unique works, broaden horizons, show appreciation, and improve the quality of clothing.